Possibilities of Using Comparative Advertising with Respect to Culture, Age, and Gender of the Recipients - Lubica GAJANOVA; Boris KOLLAR; Jana MAJEROVA (Communications of International Proceedings, 2023)
Although comparative advertising has a long tradition, its use has always been, and still is, perceived as controversial. This also corresponds to the fact that the attitude of individual cultures to comparative advertising is significantly different in various parts of the world, which is reflected in the legislative by individual state authorities. This contradictory view makes comparative advertising a current and discussed topic among experts and leads to constant discussions about its effectiveness and appropriateness of use compared to non-comparative advertising. The issue of comparative advertising is more complicated because, if the quality and the way it is processed is not considered, its impact and effectiveness vary depending on the demographic parameters of its recipients. The aim of the paper is to clarify the possibilities of using comparative advertising with respect to culture, age, and gender of the recipients.
Keywords: Comparative Advertising; Marketing Communication; Demographic Segmentation.